Prepositional Usage at the University Level - BELHOULA, Hanane (Journal of Human Sciences, 2009)
This article is an attempt towards making teachers aware of the influence and the impact of learners’ prior knowlege on their actual performances. The grammatical area investigated for this sake is prepositions which are high frequency words and of vital importance to foreign learners to understand the language and make themselves understood. However, the English prepositional system can be confusing because of the very asystematic nature of preposional rules. In addition to that, the different conceptualizations of relationships in space and time, expressed in many languages through the use of prepositions can lead to formal differences. Because of this language specificity, prepositioanl usage can be problematic to learners of English as a foreign/second language, who will have to make choices and distinctions which are not necessarily made in their language. This situation can be applicable to Algerian learners of EnglishThe results of an error analysis study carried out on a corpus of errors made by fourth year B.A students of English at the university of Constantine, concluded that in the case of prepositions, students relied on transfer, to judge the appropriate usage of prepositions.